DOI: 10.31274/rtd-180813-13735
|View full text |Cite
|
Sign up to set email alerts
|

Changes in clinical dietetics: impact of cost reduction in healthcare systems

Abstract: The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduction. In the unlikely event that the author did not send UMI a complete manuscript and there are missing pages, these will be noted. Also, if unauthorized copyright material had to be removed, a note will indicate the deletion. Oversize materials (e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In a study at this institution it was observed that The faculty in the DI at ISU, also have observed dietitians performing more technical activities, i.e. nutrition screening, than nutrition assessment and intervention (Kwon, 1999). As registered dietitians continue to strive for greater professional recognition they need to increase visibility and credibility by practicing at a higher level of clinical practice, the diagnosis and research oriented posture.…”
Section: D/ Dietetic-specific Nutritional Diagnostic Codes (D-s Ndcs)mentioning
confidence: 99%
“…In a study at this institution it was observed that The faculty in the DI at ISU, also have observed dietitians performing more technical activities, i.e. nutrition screening, than nutrition assessment and intervention (Kwon, 1999). As registered dietitians continue to strive for greater professional recognition they need to increase visibility and credibility by practicing at a higher level of clinical practice, the diagnosis and research oriented posture.…”
Section: D/ Dietetic-specific Nutritional Diagnostic Codes (D-s Ndcs)mentioning
confidence: 99%